Enriching Lives: Geriatricians’ Mission of Supportive Care for Older Persons - Virginia Boccardi (Geriatrics, 2023)
The growing older population, the increasing prevalence of chronic illnesses, and the pressing need to enhance the quality of end-of-life care have underscored the importance for geriatricians to focus on supportive and palliative measures. Within this context, the emphasis on delivering comprehensive and person-centered care has become crucial, ensuring that individuals not only receive medical treatment but also experience comfort during chronic illness and in their final days. Nevertheless, a significant number of older individuals often find themselves in hospitals during their last moments, sometimes undergoing aggressive medical interventions even when facing terminal conditions. The challenge lies in the early recognition of the end-of-life phase, initiating timely supportive and palliative care in conjunction with conventional treatments, adopting a multidisciplinary approach, and providing crucial support to grieving family members. Despite being a relatively recent field, geriatric palliative care (GPC) still requires further development. With this perspective, I aimed to shed light on the challenges and best practices for enhancing care for individuals facing chronic critical illnesses and frailty.